There is still a place for tumour‐targeted therapies in Merkel cell carcinoma in the era of immune checkpoint inhibitors. (6th September 2020) - Samimi, M.; Becker, J.
Abstract : Linked Article:  Akaike et al. Br J Dermatol 2021; 184 :319–327 .